PENERAPAN PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS DASAR PADA PELAJARAN BIOLOGI SISWA KELAS VIII SMP NEGERI 7 SURAKARTA - Ambarsari, Wiwin; Santosa, Slamet; Maridi, Maridi (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT - The research objective was to determine the effect of the application of guided inquiry approach to basic science process skills of students in grade VIII Junior High School 7 Surakarta on the basis of competency describes the circulatory systems of humans and their relationship to health. The research uses quasi-experimental research method. The population in this study were all students in grade VIII first semester of Junior High School 7 Surakarta school year 2011/2012, samples were taken with Cluster Random Sampling a number of two classes, namely class control and class experiments. Experimental class totaled 30 students and a control class numbered 30 students. To meet the requirements of the test sample is carried out initial balance ability between the experimental group and control group by t test. Research data in the form of student basic science process skills that include observation, clasifikation, measuring, prediction, conclution, and communication. Research data of basic science process skills outcomes derived from the observation sheet. Analysis of the data in this study using two-sample t test on mini tab 16. T test were selected after the test is a prerequisite Anderson-Darling normality test and Levene's homogeneity test. The results showed that application of guided inquiry learning have a significant influence on basic science process skills of students in grade VIII Junior High School 7 Surakarta. Keywords: inquiry, an inquiry guided, basic science process skills, process skill,education,biology